(untitled) (Jurnal Teknik Elektro, 2016)
System power generation of hibrida, surya cell and wind energy are represent power generation combined of two energy potency. The combining from source of this energy aim to be excess and insuffiency at each system earn each other with other system utilize to get more energy, efficiently and effective. Power plant result of hibrida power generation is planned to reach about 1000 Watt that plant of surya cell and wind energy, that connected to consument network of 1000 Watt. If surya cell is not ready to serve request of consument hence wind energi will be supply.